2021
DOI: 10.48550/arxiv.2108.10680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engineering Purcell factor anisotropy for dark and bright excitons in two dimensional semiconductors

Lekshmi Eswaramoorthy,
Sudha Mokkapati,
Anshuman Kumar

Abstract: Tightly bound dark excitons in atomically thin semiconductors can be used for various optoelectronic applications including light storage and quantum communication. Their optical accessibility is however limited due to their out-of-plane transition dipole moment. We thus propose to strengthen the coupling of dark excitons in two dimensional materials with out-of-plane resonant modes of a cavity at room temperature, by engineering the anisotropy in the Purcell factor. A silica micro-disk characterised by high c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Another way to solve this problem is to use the Purcell effect to brighten multilayered TMDCs. 31,32 This approach was successfully used to brighten Si in optical cavities. [33][34][35][36] Although due to strong free charge carriers absorption in Si, the effect was not game-changing.…”
Section: Introductionmentioning
confidence: 99%
“…Another way to solve this problem is to use the Purcell effect to brighten multilayered TMDCs. 31,32 This approach was successfully used to brighten Si in optical cavities. [33][34][35][36] Although due to strong free charge carriers absorption in Si, the effect was not game-changing.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research on van der Waals (vdW) crystals [2,4,5], supporting PhPs and PPs, have demonstrated inherent hyperbolic anisotropy and their applications in various nanophotonic devices such as infrared optical components [6][7][8], thermal emitters [9], enhanced spontaneous emission rate (SER) [10], and others [11]. In particular, anisotropic spontaneous emission rate [12,13], associated with Purcell effect [14], has great relevance for applications to light sources [10,15], quantum interference [13,16], Kerr nonlinearity enhancement [17], selective coupling to dark and bright excitons and others [18,19]. However, tunability and anisotropy of PhPs over large operational bandwidth in conventional vdW materials [2] are major limitations for enhanced anisotropic SER applications.…”
mentioning
confidence: 99%